When variety can be the spice of life: How strategic heterogeneity boosts socially responsible investment. Issue 11 (1st October 2019) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Fund managers and investors can increase financial returns from their socially responsible investment through a carefully considered strategic approach. A diversified portfolio of appropriate strategies together with an optimum intensity level perhaps best enhances the likelihood of objectives being achieved. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.